2008
DOI: 10.1128/aac.00224-08
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of High-Dose Lopinavir-Ritonavir with and without Saquinavir or Nonnucleoside Reverse Transcriptase Inhibitors in Human Immunodeficiency Virus-Infected Pediatric and Adolescent Patients Previously Treated with Protease Inhibitors

Abstract: Human immunodeficiency virus (HIV)-In 16 subjects with SQV added, the SQV median AUC was 33.7 (range, 4.4 to 76.5) g ⅐ h/ml and the median SQV C trough was 2.1 (range, 0.2 to 4.1) g/ml. At week 24, 18 of 26 (69%) subjects remained in the study. Between weeks 24 and 48, one subject withdrew for nonadherence and nine withdrew for persistently high virus load. In antiretroviral-experienced children and adolescents with HIV, high doses of LPV/r with or without SQV offer safe options for salvage therapy, but the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…(16) Another study from South Africa also demonstrated a good virologic response in children on continued LPV/r therapy, despite the presence of LPV resistance, when compared to patients who switched to an NNRTI regimen. (17) The residual benefit could be due to the high inhibitory quotient of LPV/r (18) (requiring multiple mutations to prevent resistance) and the beneficial effect of continuous drug pressure on selecting less-fit viral variants. (19) However the response rate to LPV/r in patients with PI resistance is inferior to DRV/r or TPV/r.…”
Section: Discussionmentioning
confidence: 99%
“…(16) Another study from South Africa also demonstrated a good virologic response in children on continued LPV/r therapy, despite the presence of LPV resistance, when compared to patients who switched to an NNRTI regimen. (17) The residual benefit could be due to the high inhibitory quotient of LPV/r (18) (requiring multiple mutations to prevent resistance) and the beneficial effect of continuous drug pressure on selecting less-fit viral variants. (19) However the response rate to LPV/r in patients with PI resistance is inferior to DRV/r or TPV/r.…”
Section: Discussionmentioning
confidence: 99%
“…Although they are less frequently used, some heavily pretreated children may benefit from dual PI combinations, such as LPV and SQV boosted with low‐dose RTV. In the above‐mentioned PATCG 1038 study, high‐dose LPV/r with or without SQV resulted in significant reductions in viral load and increases in CD4 cell counts at week 24 [35]. Long‐term dual therapy with standard dose LPV/r and SQV (HIV NAT‐017) has also been shown to produce significant immunological improvement and antiviral effect at week 48 [36].…”
Section: Introductionmentioning
confidence: 99%
“…The PK of abacavir were reported from the PACTG protocols P1018 and P1052;5,6 lamivudine and zidovudine data (including data on phosphorylation to the intracellular triphosphate metabolites) were collected in PACTG studies P1012 and P1052;7 lopinavir/ritonavir and saquinavir were studied in PACTG protocol P1038;8 and atazanavir was studied in PACTG protocol 1020A and in Adolescent Medicine Trials Network studies along with tenofovir 5,9. The PACTG protocol P1038 and the author’s study in children with experience of ARV suggested that the use of high doses of lopinavir/ritonavir might be required for salvage HIV therapy in adolescent patients 8,10. The Adolescent Medicine Trials Network study by Kiser et al evaluated the PK of the combined administration of atazanavir/ritonavir and tenofovir in young adults with HIV infection 9.…”
mentioning
confidence: 99%